Strategies for fostering national defense awareness in Indonesia: analysis of the 2022–2024 National Defense Index - Anton Nugroho; H.A Danang Rimbawa; Danny Setyowati; Sovian Aritonang (International Journal of Enterprise Modelling, 2026)
Strategic geopolitical shifts, digital disruption, and the rise of non-military threats require Indonesia’s national defense policy to move beyond normative and ceremonial approaches toward adaptive and measurable governance. This study analyzes the effectiveness of the National Defense Awareness Development Policy (PKBN) by examining regulatory coherence, cross-sectoral governance, and the role of the National Defense Index (IBN) as an evaluation instrument. Using a convergent mixed-methods design, this research integrates qualitative regulatory analysis with quantitative comparative analysis of IBN data from 2022 and 2024. The findings indicate that although PKBN has a relatively comprehensive legal foundation, its implementation remains administratively oriented and weakly integrated across actors. The national IBN score shows relative stability with a marginal increase, reaching 3.50 in 2024, yet significant disparities persist across regions and dimensions, particularly in Love for the Homeland (CTA) and Initial Defense Capability (KAB), with weaker performance observed in Papua and Southeast Sulawesi. These results demonstrate that IBN can function not only as an aggregate measurement tool but as a policy compass linking inputs, processes, and outcomes when supported by structured performance indicators and feedback mechanisms. Strengthening network-based governance, digitized evaluation systems, and differentiated regional interventions is therefore essential to transform PKBN into a measurable and adaptive instrument of national resilience toward Indonesia Emas 2045.